Effect of Organizational Factors on Psychological Stress and Job Satisfaction - Singh P.; Bhardwaj P.; Sharma S.K.; Mishra V. (My University, 2025)
Occupational stress is one of the most critical factors related to the employees’ well-being in any organization. Employees working in managerial positions are more prone to work-related stress because of the nature of the job and the responsibilities associated with the position. There is a lack of research on the effect of organizational factors on the psychological well-being of those working at managerial positions in the Indian context. This research aims to study the impact of workload, job control and support on psychological stress and job satisfaction. Structural equation modelling is used for the analysis. The study results reported no effect of workload on psychological stress and job satisfaction in the employees. The results also suggest that providing more control over the work can result in the better psychological well-being of employees and increase employees’ job satisfaction. © 2022 Management Development Institute.